3D printing of bone scaffolds for treating infected mandible bone defects through adjustable dual-release of chlorhexidine and osteogenic peptide. (December 2022) - Zhang, Yidi; Wang, Hanchi; Huangfu, Huimin; Zhang, Xinwei; Zhang, Hao; Qin, Qiuyue; Fu, Li; Wang, Dongyang; Wang, Chong; Wang, Lin; Zhou, Yanmin
Graphical abstract: Highlights: A hierarchical scaffold with a two-stage drug release strategy is prepared via cryo-3D printing and dipping method. The combination of chlorhexidine@graphene oxide and osteogenic peptide provides the scaffold with antibacterial and osteogenic ability. The multifunctional scaffold exerts antibacterial and osteogenic outcomes by synergistic effects in vitro . The scaffold regenerates the bone tissue effectively in an infected critical-sized mandibular bone defect in vivo . Abstract: Preventing implant-related bone infection during treating mandibular bone defect is still challenging as intractable bacterial infection in the irregular defects often leads to surgical failure and other fatal complications. Herein, we fabricate a multifunctional scaffold with controlled dual-stage drug release to achieve antibacterial and osteogenic therapy during infected bone reconstruction. Water-in-oil (w/o) β-tricalcium phosphate (TCP) nanoparticle/ poly(Lactic- co -glycolic acid) (PLGA)/dichloromethane composite emulsion inks containing the antibacterial chlorhexidine (CHX) loaded graphene oxide (GO) nanosheets and osteogenic peptide (p24) was produced through cryo-3D printing. A biphasic drug release profile is achieved via a rapid CHX release from CHX@GO on scaffold surface to kill the bacteria, and a sustained release of CHX and p24 from the scaffold matrix to prevent the recurrence of infection and induce bone regeneration. Interestingly, the GO nanosheet increased the antibacterial sensitivity through its direct physical contact which destroyed the bacteria membrane. Furthermore, the p24 and phosphate ions derived from dissociated TCP nanoparticles could induce the osteogenic differentiation of bone marrow derived stem cells. Eventually, the designed scaffolds effectively eliminated the bacteria, alleviated the accompanying inflammation, and improved bone regeneration in a rat model. The present study provides a facile strategy to treat bone defects with infection.